Hard coat film, laminate film, and method for manufacturing laminate film

The hard coat film with a plasma-processed surface and inorganic layer using low inductively coupled plasma processing addresses surface irregularities and adhesion issues, achieving improved optical and adhesive properties in anti-reflection films.

JP2025011544AActive Publication Date: 2025-01-24NITTO DENKO CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023113725
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-24
Estimated Expiration
2043-07-11

AI Technical Summary

Technical Problem

Existing anti-reflection films suffer from surface irregularities that cause light scattering and damage to the substrate due to conventional plasma treatment, leading to poor optical characteristics and adhesion issues.

Method used

A hard coat film with a plasma-processed surface using an acrylic urethane resin and controlled surface roughness, combined with an inorganic layer formed through low inductively coupled plasma processing, to enhance adhesion and optical properties.

Benefits of technology

The method ensures good optical characteristics by minimizing light scattering and improving adhesion, while reducing damage to the film, resulting in a laminated film with enhanced reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011544000001_ABST
    Figure 2025011544000001_ABST
Patent Text Reader

Abstract

To provide a hard coat film and a laminate film that excel in adhesion and have satisfactory optical characteristics, and a method for manufacturing the laminate film.SOLUTION: A hard coat film according to the present invention includes a flexible base film, and a hard coat layer on at least one side of the base film. The hard coat layer contains a cured substance of acrylic urethane resin, and the surface of the hard coat layer opposite the base film is a plasma-processed surface. The surface roughness Sa of the plasma-processed surface is 0.8 nm to 4.5 nm inclusive, and the ratio of absorbance calculated by Fourier transform infrared spectrophotometer (FT-IR) analysis satisfies a specific relationship.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hard coat film, a laminated film, and a method for producing a laminated film. [Background technology]

[0002] There is known an anti-reflection film that is disposed on the outer surface of the display screen of a display device such as a liquid crystal display and an organic electroluminescence display. Such an anti-reflection film includes, for example, an anti-reflection layer made of an inorganic material and a transparent substrate made of a resin that supports the layer, and further includes a hard coat layer provided on the anti-reflection layer side of the transparent substrate for the purpose of preventing scratches due to contact from the outside (for example, see Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2022-65437 Summary of the Invention [Problem to be solved by the invention]

[0004] The anti-reflection film described in Patent Document 1 comprises a film substrate, a hard coat layer, an adhesive layer made of an inorganic oxide, and an anti-reflection layer in this order in the thickness direction. This hard coat layer contains inorganic oxide particles (silica particles). As a result, the hard coat layer has surface irregularities on the adhesive layer side. In the anti-reflection film, the anchor effect due to the surface irregularities of the hard coat layer and the physicochemical action of the adhesive layer suppress peeling of the anti-reflection layer.

[0005] However, in the anti-reflection film of Patent Document 1, the exposed surface of the anti-reflection layer (the surface opposite to the adhesive layer) also has surface irregularities that follow the surface irregularities of the hard coat layer. The surface irregularities of the anti-reflection layer scatter a part of the light incident on the anti-reflection film. Furthermore, the silica particles in the hard coat layer also scatter a part of the light incident on the anti-reflection film. In other words, such an anti-reflection film has problems with optical properties.

[0006] In addition, a method of using capacitively coupled plasma treatment has been studied as a method of roughening the surface of a hard coat layer.By using capacitively coupled plasma treatment, the surface of the hard coat layer can be roughened without the hard coat layer containing silica particles.However, capacitively coupled plasma treatment causes a large amount of damage to the substrate film and the hard coat layer, which causes problems in adhesion with the antireflection layer and the optical properties of the antireflection film.

[0007] The present invention provides a hard coat film, a laminated film, and a method for producing a laminated film, which have excellent adhesion and good optical properties. [Means for solving the problem]

[0008] The present invention [1] provides a hard coat film comprising a flexible substrate film and a hard coat layer on at least one side of the substrate film, the hard coat layer comprising a cured product of an acrylic urethane resin, the surface of the hard coat layer opposite the substrate film being a plasma-treated surface, the surface roughness Sa of the plasma-treated surface being 0.8 nm or more and 4.5 nm or less, and the ratio of absorbances calculated by the following Fourier transform infrared spectrophotometer (FT-IR) analysis satisfies at least one of the following relationships (1) and (2): (1) A / B>72% (2) C / D>46% [FT-IR analysis] 1. The hard coat film and a substrate film with a hard coat layer, which is the hard coat film before plasma treatment (the surface of the substrate film with a hard coat layer opposite to the substrate film of the hard coat layer is a plasma untreated surface), are prepared. 2. The infrared absorption spectrum of the hard coat film is measured from the plasma-treated surface side by a total reflection measurement method using a Fourier transform infrared spectrophotometer (FT-IR), and the infrared absorption spectrum of the base film with the hard coat layer is measured from the plasma-untreated surface side by a total reflection measurement method using a Fourier transform infrared spectrophotometer (FT-IR). 3. The ratio of absorbance A to D below is calculated from the infrared absorption spectra of the hard coat film and the substrate film with the hard coat layer. A: Wavenumber 2960 cm due to CH groups in the hard coat film -1 Absorbance at 2960 ) for the C=C group at 1635 cm -1 Absorbance at 1635 ) ratio (A=Ab 1635 / Ab 2960 ) B: The ratio of absorbance at the same wavenumber as A in the substrate film with the hard coat layer (B=Ab 1635 ' / Ab 2960 ') is calculated. C: Wavenumber of 2960 cm due to CH groups in the hard coat film -1 Absorbance at 2960 ) for the C=O group at 1725 cm -1 Absorbance at 1725 ) ratio (C=Ab 1725 / Ab 2960 ) D: The ratio of absorbance at the same wavenumber as C in the substrate film with the hard coat layer (D = Ab 1725 ' / Ab 2960 ')

[0009] The present invention [2] includes the hard coat film according to the above [1], in which the absorbance ratio calculated by the following Fourier transform infrared spectrophotometer (FT-IR) analysis further satisfies the following relationship (3). (3) E / F < 155% [FT-IR analysis] 1. The hard coat film and a substrate film with a hard coat layer, which is the hard coat film before plasma treatment (the surface of the substrate film with a hard coat layer opposite to the substrate film of the hard coat layer is a plasma untreated surface), are prepared. 2. The infrared absorption spectrum of the hard coat film is measured from the plasma-treated surface side by a total reflection measurement method using a Fourier transform infrared spectrophotometer (FT-IR), and the infrared absorption spectrum of the base film with a hard coat layer is measured from the plasma-untreated surface side by a total reflection measurement method using a Fourier transform infrared spectrophotometer (FT-IR). 3. The ratio of absorbance E to absorbance F below is calculated from the infrared absorption spectra of the hard coat film and the substrate film with the hard coat layer. E: Wavenumber of 2960 cm due to CH groups in the hard coat film -1 Absorbance at 2960 ) with a wavenumber of 1524 cm due to the NH group -1 Absorbance at 1524 ) ratio (E=Ab 1524 / Ab 2960 ) F: the ratio of absorbance at the same wavenumber as E in the substrate film with the hard coat layer (F = Ab 1524 ' / Ab 2960 ')

[0010] The present invention [3] includes a laminate film comprising the hard coat film according to the above [1] or [2] and an inorganic layer disposed on the plasma-treated surface.

[0011] The present invention [4] includes the laminate film according to the above [3], in which the inorganic layer contains an indium tin composite oxide.

[0012] The present invention [5] is a method for producing a laminated film, comprising: a preparation step of preparing a long substrate film with a hard-coat layer, the substrate film having a flexible substrate film and a hard-coat layer disposed on at least one side of the substrate film, the substrate film having a first side, the first side being the side of the hard-coat layer opposite to the substrate film, and a second side opposite to the first side; a plasma treatment step of subjecting the first side of the substrate film with a hard-coat layer to a plasma treatment in a reduced pressure atmosphere in a chamber; and a deposition step of forming an inorganic layer on the first side in a reduced pressure atmosphere following the plasma treatment step, the plasma treatment being a treatment with inductively coupled plasma of an oxygen-containing gas generated by application of high-frequency power to a low-inductance antenna.

[0013] The present invention [6] includes the method for producing a laminated film described in the above [5], wherein in the plasma treatment step, the base film with a hard coat layer is transported in the chamber while being cooled or heated by a roller with a temperature control function that comes into contact with the base film with a hard coat layer.

[0014] The present invention [7] includes the method for producing a laminated film according to the above [5] or [6], wherein the low inductance antenna has a coil shape or an open loop shape.

[0015] The present invention [8] is characterized in that, in the plasma treatment step, the plasma current density at the intermediate position between the low inductance antenna and the substrate film with the hard coat layer is set to 1.0 mA / cm 3 More than 10mA / cm 3 The present invention includes a method for producing a laminated film according to any one of the above items [5] to [7], which is as follows.

[0016] The present invention [9] includes the method for producing a laminated film according to any one of the above [5] to [8], wherein in the film formation step, the inorganic layer is formed by a sputtering method, a deposition method or a chemical vapor deposition method.

[0017] The present invention

[10] includes the method for producing a laminated film according to any one of the above [5] to [9], wherein in the film-forming step, a conductive layer is formed as the inorganic layer.

[0018] The present invention

[11] includes the method for producing a laminated film according to any one of the above [5] to [9], wherein in the film formation step, an antireflection layer is formed as the inorganic layer, and the antireflection layer includes a plurality of transparent inorganic oxide films laminated in a thickness direction. Effect of the Invention

[0019] As described above, the hard coat film of the present invention has a surface roughness Sa of 0.8 nm or more and 4.5 nm or less on the plasma-treated surface. Therefore, the hard coat film can suppress light scattering, and while having good optical properties, can ensure adhesion due to roughening of the plasma-treated surface. Also, as described above, the ratio of absorbances calculated by Fourier transform infrared spectrophotometer (FT-IR) analysis satisfies a specific relationship. Therefore, the influence of plasma treatment on the hard coat film can be suppressed, and as a result, the hard coat film has excellent optical properties while ensuring adhesion.

[0020] The laminated film of the present invention includes the hard coat film of the present invention, and therefore peeling of the inorganic layer from the hard coat film can be suppressed, the reliability of the laminated film can be improved, and the laminated film has good optical properties.

[0021] In the method for producing a laminated film of the present invention, a first surface of a substrate film with a hard coat layer is treated with inductively coupled plasma of an oxygen-containing gas generated by application of high-frequency power to a low-inductance antenna. This type of plasma treatment can reduce damage to the hard coat film compared to conventional capacitively coupled plasma treatments, and can produce a laminated film with excellent optical properties while ensuring adhesion. In addition, the first surface of the hard coat film can be roughened, thereby improving adhesion to the inorganic layer. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 is a cross-sectional view of one embodiment of the hard coat film of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of one embodiment of the laminated film of the present invention. [Diagram 3] FIG. 3 shows a case where the inorganic layer of the laminate film shown in FIG. 2 has a laminate structure of an adhesive layer and an antireflection layer. [Figure 4] 4A to 4C show one embodiment of the method for producing a laminated film of the present invention, in which Fig. 4A shows a step of preparing a substrate film with a hard coat layer, Fig. 4B shows a step of performing a plasma treatment, and Fig. 4C shows a step of forming an inorganic layer. [Diagram 5] FIG. 5 is a schematic diagram of an apparatus for carrying out the plasma treatment step and the film formation step in the method for producing a laminated film. [Figure 6] 7 is a perspective view showing the positional relationship between a low inductance antenna and a hard coat film in the plasma processing chamber shown in FIG. 6. [Figure 7] 8 is a cross-sectional view showing the positional relationship between a low inductance antenna and a hard coat film in the plasma processing chamber shown in FIG. 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] 1.Hard coat film The hard coat film X of the present invention will be described with reference to FIG.

[0024] The hard coat film X includes a flexible base film and a hard coat layer disposed on at least one surface of the base film. Specifically, the hard coat film X includes a base film 11 and a hard coat layer 12 in this order in the thickness direction H'. The base film 11 and the hard coat layer 12 are in contact with each other. The hard coat film X extends in a direction (plane direction D') perpendicular to the thickness direction H'.

[0025] <Base film> The base film 11 is a supporting film that ensures the strength of the hard coat film X. The base film 11 is, for example, a transparent resin film having flexibility.

[0026] Examples of materials for the base film 11 include polyester resin, polyolefin resin, cellulose resin, acrylic resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, polyimide resin, and polystyrene resin.

[0027] Examples of polyester resins include polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate.

[0028] Examples of polyolefin resins include polyethylene, polypropylene, and cycloolefin polymer (COP).

[0029] An example of the cellulose resin is triacetyl cellulose (TAC).

[0030] The material of the base film 11 may be used alone or in combination of two or more kinds.

[0031] From the viewpoints of transparency and strength, the material of the base film 11 is preferably at least one selected from the group consisting of polyester resin, polyolefin resin, and cellulose resin, more preferably at least one selected from the group consisting of PET, COP, and TAC, and even more preferably TAC.

[0032] Moreover, it is preferable that the base film 11 does not contain particles (for example, metal oxide particles, which will be described later).

[0033] The thickness of the base film 11 is, for example, 10 μm or more, preferably 20 μm or more, more preferably 30 μm or more, and for example, 200 μm or less, preferably 150 μm or less, more preferably 100 μm or less, and even more preferably 70 μm or less.

[0034] When the thickness of the base film 11 is equal to or greater than the above lower limit, the strength of the hard coat film X can be ensured. When the thickness of the base film 11 is equal to or less than the above upper limit, the handleability of the hard coat film X in a roll-to-roll process described below can be ensured. When a hard coat layer is disposed on only one side of the base film 11, a carrier film (not shown) may be attached to the side of the base film 11 opposite the hard coat layer 12 in order to ensure transportability and handleability of the base film 11 in the roll-to-roll process.

[0035] The total light transmittance (JIS K 7375:2008) of the base film 11 is, for example, 80% or more, preferably 85% or more, more preferably 90% or more, and for example, 100% or less.

[0036] When the total light transmittance of the base film 11 is equal to or greater than the above lower limit, good transparency can be ensured in the hard coat film X.

[0037] <Hard coat layer> The hard coat layer 12 is a layer that makes it difficult for scratches to form on the exposed surface of a layer (inorganic layer 20 in the laminate film Y shown in Figure 2) formed on the surface 12a (plasma-treated surface 12a described later) of the hard coat layer 12 opposite the base film 11.

[0038] The hard coat layer 12 is a layer of a cured product of a composition containing an ultraviolet curable resin (an ultraviolet curable resin composition).

[0039] The ultraviolet-curable resin composition contains an acrylic urethane resin as an ultraviolet-curable resin, and therefore the hard coat layer 12 contains a cured product of the acrylic urethane resin.

[0040] The ultraviolet-curable resin composition may contain an ultraviolet-curable resin other than the acrylic urethane resin.

[0041] Other ultraviolet curable resins include, for example, polyester resin, acrylic resin (excluding acrylic urethane resin), urethane resin (excluding acrylic urethane resin), amide resin, silicone resin, epoxy resin, and melamine resin.

[0042] These resins may be used alone or in combination with other ultraviolet curable resins.

[0043] The ultraviolet-curable resin composition may or may not contain particles.

[0044] Particles include, for example, organic particles and inorganic particles.

[0045] Examples of materials for the organic particles include polymethyl methacrylate, polystyrene, acrylic-styrene copolymers, and polycarbonate.

[0046] Examples of inorganic particles include inorganic oxide particles. Examples of materials for inorganic oxide particles include metal oxides and semi-metal oxides, specifically, silica, alumina, titania, zirconia, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide. The materials for inorganic oxide particles may be metal composite oxides in which the above-mentioned metal oxides are composited. In addition, functional groups such as acrylic groups and epoxy groups may be introduced on the surface of the inorganic oxide particles in order to increase the adhesion and affinity with the resin.

[0047] The average particle size of the organic particles is not particularly limited.

[0048] The average particle size of the inorganic particles is, for example, 200 nm or less, preferably 100 nm or less, and more preferably 50 nm or less.

[0049] The average particle size can be measured by a specific surface area measurement (BET) method.

[0050] The content of the organic particles in the ultraviolet-curable resin composition (solid content) is not particularly limited.

[0051] When the average particle diameter of the inorganic particles is 20 nm or more, the content of the inorganic particles in the ultraviolet-curable resin composition (solid content) is, for example, less than 20 mass%, preferably 15 mass% or less, more preferably 10 mass% or less, even more preferably 5 mass% or less, particularly preferably 1 mass% or less, and most preferably 0 mass%.

[0052] When the average particle size of the inorganic particles is less than 20 nm, the content of the inorganic particles in the ultraviolet-curable resin composition (solid content) is not particularly limited, but is, for example, 20 mass % or less, preferably 15 mass % or less, more preferably 10 mass % or less, even more preferably 5 mass % or less, particularly preferably 1 mass % or less, and most preferably 0 mass %.

[0053] When the content ratio of the particles in the ultraviolet-curable resin composition (solid content) is equal to or less than the above upper limit, scattering of light incident on the hard coat film X caused by the particles in the hard coat film X can be suppressed.

[0054] The thickness of the hard coat layer 12 is, for example, 1 μm or more, preferably 2 μm or more, and for example, 50 μm or less, preferably 40 μm or less, more preferably 35 μm or less, and still more preferably 30 μm or less.

[0055] When the thickness of the hard coat layer 12 is equal to or greater than the above lower limit, the scratch resistance of the hard coat layer 12 can be ensured. When the thickness of the hard coat layer 12 is equal to or less than the above upper limit, the transparency of the hard coat layer 12 can be ensured.

[0056] The hard coat layer 12 has a plasma-treated surface 12a on the side opposite to the base film 11. In other words, the surface of the hard coat layer 12 opposite to the base film 11 is the plasma-treated surface 12a.

[0057] The surface roughness Sa (arithmetic mean height based on ISO 25178-2:2012) of the plasma-treated surface 12a is 0.80 nm or more, preferably 1.00 nm or more, more preferably 1.20 nm or more, and even more preferably 1.25 nm or more. The surface roughness Sa (arithmetic mean height based on ISO 25178-2:2012) of the plasma-treated surface 12a is 4.50 nm or less, preferably 3.50 nm or less, more preferably 3.00 nm or less, even more preferably 2.50 nm or less, and particularly preferably 2.00 nm or less.

[0058] When the surface roughness Sa of the plasma-treated surface 12a is equal to or greater than the lower limit, the fine irregularities of the plasma-treated surface 12a have an anchoring effect on a layer (inorganic layer 20 in the case of laminate film Y shown in FIG. 2) formed on the plasma-treated surface 12a, thereby improving adhesion of the layer to the hard coat film X. When the surface roughness Sa of the plasma-treated surface 12a is equal to or less than the upper limit, excessive irregularities on the plasma-treated surface 12a can be suppressed, ensuring mechanical strength.

[0059] The plasma-treated surface 12a is a surface that has been plasma-treated. The plasma treatment is described in detail below, but from the viewpoint of suppressing changes in the state of chemical bonds in the hard coat film X, it is preferably a treatment by inductively coupled plasma using an oxygen-containing gas generated by application of high-frequency power to a low-inductance antenna (oxygen plasma treatment). The oxygen plasma treatment will be described in detail in the manufacturing method of the laminated film Y (shown in FIG. 2) described below.

[0060] The color value (b*) of the hard coat film X, calculated by the procedure described below, is, for example, −0.7 or more, preferably −0.6 or more, more preferably −0.57 or more, even more preferably −0.55 or more, and for example, 0.7 or less, preferably 0.6 or less, more preferably 0.57 or less, even more preferably 0.55 or less.

[0061] When the color value (b*) of the hard coat film X is within the above range, good transparency can be ensured in the hard coat film X.

[0062] The difference (|b*-b*'|) between the color value (b*) of the hard coat film X and the color value (b*') of the substrate film X' with a hard coat layer described below is, for example, 0.17 or less, preferably 0.15 or less, more preferably 0.10 or less, even more preferably 0.05 or less, and particularly preferably 0.03 or less.

[0063] When the difference (|b*-b*'|) between the color value (b*) of the hard coat film X and the color value (b*') of the base film X' with a hard coat layer is equal to or less than the upper limit, the difference between the hard coat film X and the base film X' with a hard coat layer is small, and the optical properties are excellent.

[0064] The color value (b*) of the hard coat film X will be described in detail in the Examples below. The transmittance of the hard coat film X is measured using an ultraviolet-visible-infrared spectrophotometer, and the color value (b*) can be calculated using a color calculation program based on the measured values ​​of the transmittance at each wavelength from 380 nm to 780 nm.

[0065] In the hard coat film X, the ratio of absorbances calculated by the following Fourier transform infrared spectrophotometer analysis (FT-IR analysis) satisfies the relationship described below.

[0066] Specifically, in the hard coat film X, at least one of the following A1 / B1 and C1 / D1 is within the following range, preferably, both of the following A1 / B1 and C1 / D1 are within the following range, more preferably, further, the following E1 / F1 is within the following range, and particularly preferably, further, at least one of the following G1 / H1 and I1 / J1 is within the following range.

[0067] (FT-IR analysis) 1. Prepare a hard coat film X and a substrate film X' with a hard coat layer, which is the hard coat film X before plasma treatment (see FIG. 4A) (in the substrate film X' with a hard coat layer, a surface 12a' of the hard coat layer 12 opposite the substrate film 11 is a plasma untreated surface 12a'). 2. The infrared absorption spectrum of the hard coat film X is measured from the plasma-treated surface 12a side by total reflection measurement using a Fourier transform infrared spectrophotometer (FT-IR), and the infrared absorption spectrum of the hard coat layer-coated substrate film X' is measured from the plasma-untreated surface 12a' side by total reflection measurement (ATR method) using a Fourier transform infrared spectrophotometer (FT-IR). 3. The ratio of absorbances A1 to J1 below is calculated from the infrared absorption spectra of the hard coat film X and the substrate film X' with a hard coat layer.

[0068] A1: Wave number 2960 cm due to CH groups in hard coat film X -1 Absorbance at 2960 ) for the C=C group at 1635 cm -1 Absorbance at 1635 ) ratio (A1=Ab 1635 / Ab 2960 ) B1: The ratio of absorbance at the same wavenumber as A1 in the substrate film X' with a hard coat layer (B1 = Ab 1635 ' / Ab 2960 ') C1: Wave number 2960 cm due to CH groups in hard coat film X -1 Absorbance at 2960 ) for the C=O group at 1725 cm -1 Absorbance at 1725 ) ratio (C1 = Ab 1725 / Ab 2960 ) D1: The ratio of absorbance at the same wavenumber as C1 in the substrate film X' with a hard coat layer (D1=Ab 1725 ' / Ab 2960 ') E1: Wavenumber 2960 cm due to CH groups in hard coat film X -1 Absorbance at 2960 ) with a wavenumber of 1524 cm due to the NH group -1 Absorbance at 1524 ) ratio (E1=Ab 1524 / Ab2960 ) F1: The ratio of absorbance at the same wavenumber as E1 in the substrate film X' with a hard coat layer (F1=Ab 1524 ' / Ab 2960 ') G1: Wave number 2960 cm due to CH group in hard coat film X -1 Absorbance at 2960 ) for the C=C group at 810 cm -1 Absorbance at 810 ) ratio (G1=Ab 810 / Ab 2960 ) H1: The ratio of absorbance at the same wavenumber as G1 in the substrate film X' with a hard coat layer (H1 = Ab 810 ' / Ab 2960 ') I1: Wavenumber 2960 cm due to CH groups in hard coat film X -1 Absorbance at 2960 ) with a wave number of 1159 cm due to the CO group -1 Absorbance at 1159 ) ratio (I1 = Ab 1159 / Ab 2960 ) J1: The ratio of absorbance at the same wavenumber as I1 in the substrate film X' with a hard coat layer (J1=Ab 1159 ' / Ab 2960 ')

[0069] Note that each of the wave numbers described above in A1 to J1 is a wave number indicating the peak position due to the corresponding chemical bond, and may vary slightly. Also, some deviation may occur due to measurement fluctuations. Therefore, each of the wave numbers described above is within ±10 cm -1 A degree of deviation is permitted.

[0070] Furthermore, A1 / B1, C1 / D1, E1 / F1, G1 / H1, and I1 / J1 described later quantitatively indicate the extent to which the state of chemical bonds in the substrate film X' with a hard coat layer has changed after plasma treatment, and show the amount of change (%) when the state of chemical bonds in the substrate film X' with a hard coat layer is taken as 100%.

[0071] A1 / B1 is more than 72%, preferably 73% or more, more preferably 75% or more, and further preferably 77% or more.

[0072] C1 / D1 is more than 46%, preferably 50% or more, more preferably 55% or more, even more preferably 60% or more, and particularly preferably 65% ​​or more.

[0073] E1 / F1 is, for example, less than 155%, preferably 150% or less, more preferably 145% or less, even more preferably 140% or less, and particularly preferably 135% or less.

[0074] G1 / H1 is, for example, more than 50%, preferably 55% or more, more preferably 60% or more, and even more preferably 65% ​​or more.

[0075] I1 / J1 is, for example, more than 50%, preferably 55% or more, more preferably 60% or more, and even more preferably 65% ​​or more.

[0076] When A1 / B1, C1 / D1, E1 / F1, G1 / H1, and I1 / J1 are within the above ranges, the change in the state of chemical bonds in the hard coat film X relative to the hard coat layer-attached substrate film X' can be suppressed, and thus such a hard coat film X has excellent optical properties while ensuring adhesion.

[0077] Specifically, A1 / B1 and G1 / H1 represent the change in C=C before and after the plasma treatment, and C1 / D1 represents the change in C=O before and after the plasma treatment. I1 / J1 represents the change in CO before and after plasma treatment. A1 / B1, C1 / D1, G1 / H1, and I1 / J1 being values ​​within the above ranges means that the decrease in C=C, C=O, and CO due to plasma treatment is suppressed, that is, the damage caused by plasma treatment to the inside of the hard coat film X is reduced. Therefore, the influence on the optical properties is suppressed. In addition, since the plasma treatment is a treatment near the surface of the hard coat layer 12, it increases the surface roughness and brings about an anchor effect. Therefore, when an inorganic layer is laminated on the plasma-treated surface 12a, chemical bonds are formed between the plasma-treated surface 12a and the inorganic layer via carbon and oxygen, which can improve adhesion, and further improve adhesion due to the anchor effect.

[0078] E1 / F1 represents the change in NH before and after plasma treatment. The fact that E1 / F1 is within the above range means that the plasma treatment suppresses an excessive increase in NH, which also shows that damage to the inside of the hard coat film X caused by the plasma treatment is reduced.

[0079] In addition, the target wavenumbers of A1 / B1, C1 / D1, and E1 / F1 are those derived from organic matter, and are relatively on the long wavenumber side, and have less noise compared to the short wavenumber side, so that the change in the state of chemical bonds can be confirmed more clearly. In other words, if A1 / B1, C1 / D1, and E1 / F1 are values ​​within the above ranges, the change in the state of chemical bonds in the hard coat film X relative to the substrate film X' with a hard coat layer can be suppressed, and thus such a hard coat film X has excellent optical properties while ensuring adhesion.

[0080] In other words, in the hard coat film X, the ratio of absorbances calculated by the above-mentioned Fourier transform infrared spectrophotometer analysis (FT-IR analysis) satisfies at least one of the following relationships (1) and (2). As a result, excellent optical properties are achieved while ensuring adhesion. Preferably, the hard coat film X satisfies both the following relationships (1) and (2). More preferably, the hard coat film X further satisfies the following relationship (3). As a result, even more excellent optical properties are achieved while ensuring adhesion.

[0081] (1) A1 / B1>72% (2) C1 / D1>46% (3) E1 / F1<155%

[0082] In the hard coat film X, as described above, the surface roughness Sa1 of the surface 12a (plasma-treated surface 12a) of the hard coat layer 12 (cured layer of the ultraviolet-curable resin composition containing an acrylic urethane resin) opposite to the base film 11 is 0.80 nm or more and 4.50 nm or less, and the ratio of the absorbances of the hard coat film X calculated by the above-mentioned Fourier transform infrared spectrophotometer analysis (FT-IR analysis) satisfies the above-mentioned relationship between (1) and (2). The surface roughness Sa of the hard coat layer 12 being 0.80 nm or more and 4.50 nm or less means that when an inorganic layer is formed on the hard coat layer 12, the anchor effect of the hard coat layer 12 on the inorganic layer enhances the adhesion of the inorganic layer to the hard coat film X. In addition, the ratio of the absorbances satisfying the above-mentioned relationship between (1) and (2) indicates that the hard coat film X has excellent optical properties while ensuring adhesion.

[0083] 2.Laminated film With reference to FIG. 2, a laminated film Y according to one embodiment of the present invention will be described.

[0084] The laminated film Y includes a hard coat film X and an inorganic layer 20 disposed on the plasma-treated surface 12a of the hard coat film X. Specifically, the laminated film Y includes the hard coat film X and the inorganic layer 20 disposed on the plasma-treated surface 12a of the hard coat film X, in this order in the thickness direction H'. That is, the inorganic layer 20 and the hard coat layer 12 are in contact with each other. Such a laminated film Y extends in a direction (plane direction D') perpendicular to the thickness direction H'.

[0085] <Inorganic layer> Examples of the inorganic layer 20 include an anti-reflective layer and a conductive layer. The anti-reflective layer is a layer having anti-reflective properties that suppresses the reflection intensity of external light. The conductive layer is a layer having conductivity. The inorganic layer 20 may be a layer other than the anti-reflective layer and the conductive layer (for example, an adhesive layer). The inorganic layer 20 may also be a composite layer including an anti-reflective layer and another layer. The inorganic layer 20 may also be a composite layer including a conductive layer and another layer. FIG. 3 shows a case where the inorganic layer 20 has a laminated structure of an adhesive layer 21 and an anti-reflective layer 22.

[0086] Examples of the inorganic layer 20 include a metal layer and a metal oxide layer. The metal oxide layer is formed of, for example, an indium tin composite oxide, silicon oxide, aluminum oxide, etc. The inorganic layer 20 preferably contains an indium tin composite oxide.

[0087] [Adhesion layer] The adhesion layer 21 is disposed on the plasma-treated surface 12a of the hard coat film X. That is, the adhesion layer 21 is in contact with the hard coat layer 12. Such an adhesion layer 21 is a layer that enhances the adhesion of other inorganic layers 20 (e.g., an anti-reflection layer and a conductive layer) laminated on the adhesion layer 21 to the hard coat film X.

[0088] Examples of the material of the adhesive layer 21 include metals such as Si, In, Ni, Cr, Ar, Sn, Au, Ag, Pt, Zn, Ti, W, Zr, Pd, and Nb, alloys of two or more of these metals, and oxides of these metals. From the viewpoint of compatibility between adhesion to both the hard coat film X and the inorganic layer 20 (e.g., anti-reflection layer and conductive layer) laminated on the adhesive layer 21 and transparency of the adhesive layer 21, the material of the adhesive layer 21 is preferably an inorganic oxide containing at least one element selected from the group consisting of Si, In, Al, Sn, Ti, and Zr. From the viewpoint of compatibility between adhesion to both the hard coat film X and the inorganic layer 20 (e.g., anti-reflection layer and conductive layer) laminated on the adhesive layer 21 and transparency of the adhesive layer 21, the material of the adhesive layer 21 is more preferably indium tin composite oxide (ITO) and silicon oxide (SiOx), and even more preferably ITO.

[0089] Silicon oxide as the material of the adhesion layer 21 is, for example, SiOx having a smaller amount of oxygen than the stoichiometric composition, and preferably SiOx where x is 1.2 or more and 1.9 or less.

[0090] The thickness of the adhesion layer 21 is, for example, 0.1 nm or more, preferably 0.5 nm or more, more preferably 1.0 nm or more, and for example, 30 nm or less, preferably 20 nm or less, more preferably 15 nm or less.

[0091] When the thickness of the adhesive layer 21 is equal to or greater than the above lower limit, the adhesive strength between the hard coat film X and the inorganic layer 20 (e.g., an anti-reflection layer and a conductive layer) laminated on the adhesive layer 21 can be ensured. When the thickness of the adhesive layer 21 is equal to or less than the above upper limit, the transparency of the adhesive layer 21 can be ensured.

[0092] [Anti-reflection layer] The antireflection layer 22 is disposed, for example, on one surface in the thickness direction H' of the adhesive layer 21. The antireflection layer 22 includes, for example, a plurality of transparent inorganic oxide films stacked in the thickness direction H'.

[0093] The antireflection layer is, for example, an alternate laminate of high refractive index layers and low refractive index layers. The number of layers in the alternate laminate is not particularly limited, and is, for example, four layers.

[0094] More specifically, the antireflection layer 22 shown in FIG. 3 includes a high refractive index layer 22a, a low refractive index layer 22b, a high refractive index layer 22c, and a low refractive index layer 22d, in this order from the adhesion layer 21 side in the thickness direction H'.

[0095] The high refractive index layer 22a is in contact with the adhesive layer 21. The high refractive index layer 22a and the low refractive index layer 22b are in contact. The low refractive index layer 22b and the high refractive index layer 22c are in contact. The high refractive index layer 22c and the low refractive index layer 22d are in contact.

[0096] The high refractive index layers 22a and 22c are layers having a relatively high refractive index, and the low refractive index layers 22b and 22d are layers having a relatively low refractive index.

[0097] In such a laminated structure, the intensity of the reflected light is attenuated by the interference between the reflected light at multiple interfaces in the high refractive index layers 22a, 22c and the low refractive index layers 22b, 22d. Such interference can be realized by adjusting the optical film thickness (the product of the refractive index and the thickness of the film) of each layer of the inorganic layer 20.

[0098] The high refractive index layer 22a (first high refractive index layer) is made of a high refractive index material having a refractive index of 1.9 or more at a wavelength of 550 nm. Examples of the high refractive index material include niobium oxide (Nb2O5), titanium oxide, zirconium oxide, indium tin oxide (ITO), and antimony tin oxide (ATO). From the viewpoint of achieving both a high refractive index and low absorption of visible light, the high refractive index material is preferably niobium oxide (refractive index 2.33).

[0099] The optical thickness of the high refractive index layer 22a is, for example, 20 nm or more and, for example, 55 nm or less.

[0100] The low refractive index layer 22b (first low refractive index layer) is made of a low refractive index material having a refractive index of 1.6 or less at a wavelength of 550 nm. Examples of the low refractive index material include silicon dioxide (SiO2) and magnesium fluoride. From the viewpoint of achieving both a low refractive index and low absorption of visible light, the low refractive index material is preferably silicon dioxide (refractive index 1.46).

[0101] The optical thickness of the low refractive index layer 22b is, for example, 15 nm or more and, for example, 70 nm or less.

[0102] The high refractive index layer 22c (second high refractive index layer) is made of a high refractive index material having a refractive index of 1.9 or more at a wavelength of 550 nm. Examples of the high refractive index material include the materials described above for the high refractive index layer 22a, and preferably niobium oxide.

[0103] The optical thickness of the high refractive index layer 22c is, for example, 60 nm or more and, for example, 330 nm or less.

[0104] The low refractive index layer 22d (second low refractive index layer) is made of a low refractive index material having a refractive index of 1.6 or less at a wavelength of 550 nm. Examples of the low refractive index material include the materials described above for the low refractive index layer 22b, and preferably silicon dioxide.

[0105] The optical thickness of the low refractive index layer 22d is, for example, 100 nm or more and, for example, 160 nm or less.

[0106] The total thickness of the antireflection layer 22 is, for example, 180 nm or more, preferably 200 nm or more, more preferably 220 nm or more, and for example, 320 nm or less, preferably 280 nm or less, more preferably 250 nm or less. In this embodiment, the total thickness of the antireflection layer 22 is the sum of the thicknesses of the high refractive index layers 22a and 22c and the low refractive index layers 22b and 22d.

[0107] If the total thickness of the antireflection layer 22 is equal to or greater than the above lower limit, the function of attenuating the reflected light intensity can be ensured in the antireflection layer 22. If the total thickness of the antireflection layer 22 is equal to or less than the above upper limit, cracking of the antireflection layer 22 can be suppressed.

[0108] [Conductive layer] The conductive layer is, for example, a layer made of a conductive material, although not shown.

[0109] Conductive materials include, for example, metals and metal oxides.

[0110] Examples of metals include copper, silver, gold, aluminum, and alloys thereof.

[0111] Examples of metal oxides include indium-containing conductive oxides, antimony-containing conductive oxides, and zinc-containing conductive oxides. Examples of indium-containing conductive oxides include indium tin oxide (ITO), indium zinc oxide (IZO), indium gallium oxide (IGO), and indium gallium zinc oxide (IGZO). Examples of antimony-containing conductive oxides include antimony tin oxide (ATO). Examples of zinc-containing conductive oxides include zinc aluminum oxide (AZO).

[0112] The conductive layer has a thickness of, for example, 10 nm or more, preferably 15 nm or more, more preferably 20 nm or more, and for example, 1000 nm or less, preferably 800 nm or less, more preferably 500 nm or less, and even more preferably 200 nm or less.

[0113] The laminate film Y preferably has the ratios A2 / B2, C2 / D2, E2 / F2, G2 / H2, and I2 / J2, which are calculated using the ratios of absorbance calculated by the Fourier transform infrared spectrophotometer analysis (FT-IR analysis) described below, within the ranges described below.

[0114] (FT-IR analysis) 1. Prepare a laminate film Y and a substrate film X' with a hard coat layer, which is the hard coat film X before plasma treatment (see FIG. 4A) (in the substrate film X' with a hard coat layer, a surface 12a' of the hard coat layer 12 opposite the substrate film 11 is a plasma untreated surface 12a'). 2. The infrared absorption spectrum of the laminate film Y is measured from the surface side of the inorganic layer 20 of the laminate film Y by the attenuated total reflection method (ATR method) using a Fourier transform infrared spectrophotometer (FT-IR), and the infrared absorption spectrum of the base film X' with a hard coat layer is measured from the plasma untreated surface 12a' side by the attenuated total reflection method (ATR method) using a Fourier transform infrared spectrophotometer (FT-IR). 3. The ratios of absorbances A2 to J2 below are calculated from the infrared absorption spectra of the laminate film Y and the substrate film X' with a hard coat layer.

[0115] It should be noted that B2, D2, F2, H2, and J2 are the same as B1, D1, F1, H1, and J1 described above, respectively, and therefore will be omitted.

[0116] A2: Wave number 2960 cm due to CH groups in laminate film Y -1 Absorbance at 2960 ) for the C=C group at 1635 cm -1 Absorbance at 1635 ) ratio (A2=Ab 1635 / Ab 2960 ) C2: Wave number 2960 cm due to CH groups in laminate film Y -1 Absorbance at 2960 ) for the C=O group at 1725 cm -1 Absorbance at 1725 ) ratio (C2 = Ab 1725 / Ab 2960 ) E2: Wave number 2960 cm due to CH groups in laminate film Y -1 Absorbance at 2960) with a wavenumber of 1524 cm due to the NH group -1 Absorbance at 1524 ) ratio (E2=Ab 1524 / Ab 2960 ) G2: Wave number 2960 cm due to CH groups in laminated film Y -1 Absorbance at 2960 ) for the C=C group at 810 cm -1 Absorbance at 810 ) ratio (G2=Ab 810 / Ab 2960 ) I2: Wave number 2960 cm due to CH groups in laminate film Y -1 Absorbance at 2960 ) with a wave number of 1159 cm due to the CO group -1 Absorbance at 1159 ) ratio (I2=Ab 1159 / Ab 2960 )

[0117] Note that each of the wave numbers described in A2 to J2 above is a wave number indicating the peak position due to the corresponding chemical bond, and may vary slightly. Also, some deviation may occur due to measurement fluctuations. Therefore, each of the wave numbers described above is within ±10 cm -1 A degree of deviation is permitted.

[0118] Furthermore, A2 / B2, C2 / D2, E2 / F2, G2 / H2, and I2 / J2 described later quantitatively indicate the extent to which the state of chemical bonds in the substrate film X' with a hard coat layer has changed after lamination of the inorganic layer, and indicate the amount of change when the state of chemical bonds in the substrate film X' with a hard coat layer is taken as 100%.

[0119] A2 / B2 is, for example, more than 63%, preferably 70% or more, more preferably 80% or more, even more preferably 85% or more, and particularly preferably 90% or more.

[0120] C2 / D2 is, for example, more than 26%, preferably 50% or more, more preferably 70% or more, even more preferably 80% or more, and particularly preferably 88% or more.

[0121] E2 / F2 is, for example, less than 216%, preferably 200% or less, more preferably 180% or less, even more preferably 160% or less, and particularly preferably 150% or less.

[0122] G2 / H2 is, for example, more than 34%, preferably 50% or more, more preferably 60% or more, and further preferably 70% or more.

[0123] I2 / J2 is, for example, more than 29%, preferably 50% or more, more preferably 70% or more, even more preferably 90% or more, and particularly preferably 95% or more.

[0124] When A2 / B2, C2 / D2, E2 / F2, G2 / H2, and I2 / J2 are within the above ranges, changes in the state of chemical bonds inside the laminate film Y relative to the hard-coat layer-attached substrate film X' can be suppressed, and thus such a laminate film Y has excellent optical properties.

[0125] In particular, A2 / B2, C2 / D2, and E2 / F2 target wavenumbers derived from organic matter, which are relatively on the long wavenumber side and have less noise compared to the short wavenumber side, so that it is possible to more clearly confirm the change in the state of chemical bonds due to the plasma treatment inside the laminate film Y. In other words, if A2 / B2, C2 / D2, and E2 / F2 are values ​​within the above ranges, it is possible to suppress the change in the state of chemical bonds inside the laminate film Y relative to the base film X' with a hard coat layer, and thus such a laminate film Y has excellent optical properties.

[0126] The peeling rate of the inorganic layer 20 of the laminated film Y in the second test described below after the first test (accelerated weather resistance test) described below is, for example, 25% or less, preferably 10% or less, more preferably 5% or less, even more preferably 3% or less, and particularly preferably 1% or less, from the viewpoint of ensuring the adhesion of the inorganic layer 20. The methods of the first and second tests are described more specifically in the Examples.

[0127] If the peeling rate of the inorganic layer 20 is equal to or less than the above upper limit, the substantial deterioration of the function of the inorganic layer 20 due to peeling of the inorganic layer 20 can be suppressed, and the laminated film Y has excellent reliability.

[0128] Test 1: First, the exposed surface of the base film 11 in the laminated film Y is fixed to a glass plate. Next, the inorganic layer 20 of the laminated film Y on the glass plate is irradiated with light from a metal halide lamp using a weathering tester for 32.5 hours (accelerated weathering test). Other conditions include a temperature of 85°C, a relative humidity of 45%, and an irradiation intensity (integrated illuminance from 290 to 450 nm) of 150 mW / cm. 2 Let us assume that.

[0129] Test 2: First, eleven parallel first incisions (1 mm apart) extending linearly in a first direction and eleven parallel second incisions (1 mm apart) extending linearly in a second direction perpendicular to the first direction are formed in the inorganic layer 20 of the laminated film Y on the glass plate after the first test using a cutter knife, and 100 grids are formed by the first and second incisions. Next, a polyester wiper is slid over the 100 grid areas of the laminated film Y while continuously dropping isopropyl alcohol at 2 mL / min. The sliding conditions are a wiper contact surface of 20 mm x 20 mm, a load of 1.5 kg / 20 mm, a sliding speed of 50 mm / sec, and 1000 reciprocations. Next, 1 mm of the 100 grids are removed. 2 Count the number of squares where the above peeling occurred. Divide the count by 100 to calculate the peeling rate (%).

[0130] As described above, the laminated film Y includes the hard coat film X and the inorganic layer 20 disposed on the plasma-treated surface 12a of the hard coat film X. As described above, in the hard coat film X, the surface roughness Sa of the plasma-treated surface 12a of the hard coat layer 12 (a cured layer of an ultraviolet-curable resin composition containing an acrylic urethane resin) on the side opposite to the substrate film 11 is 0.80 nm or more and 4.50 nm or less, and the ratio of the absorbances of the hard coat film X calculated by the above-mentioned Fourier transform infrared spectrophotometer analysis (FT-IR analysis) satisfies the above-mentioned relationships (1) and (2). In the laminated film Y, the surface roughness Sa of the hard coat layer 12 is 0.80 nm or more and 4.50 nm or less, and this increases the adhesion of the inorganic layer 20 to the hard coat film X due to the anchor effect of the hard coat layer 12 on the inorganic layer 20 on the hard coat layer 12. Moreover, the ratio of the absorbances satisfies the relationship between (1) and (2) above, which indicates that the laminate film Y has excellent optical properties while ensuring the adhesion of the inorganic layer 20 to the hard coat film X. Such a laminate film Y has excellent optical properties and is also excellent in reliability.

[0131] 3.Laminated film manufacturing method (how to use hard coat film) A method for producing the laminated film Y will be described with reference to FIGS. 4A to 4C.

[0132] The method for producing the laminated film Y includes, for example, a preparation step (FIG. 4A) of preparing a long substrate film X' with a hard coat layer, a plasma treatment step (FIG. 4B) of subjecting the substrate film X' with a hard coat layer to a plasma treatment, and a film formation step (FIG. 4C) of forming an inorganic layer 20. The plasma treatment step and the film formation step are sequentially performed using an apparatus Z as shown in FIG.

[0133] (Preparation process) In the preparation step, as shown in Fig. 4A, a long substrate film X' with a hard coat layer is prepared, which includes a flexible substrate film 11 and a hard coat layer 12 disposed on at least one side of the substrate film 11. The long substrate film X' with a hard coat layer has a first side 12a', which is the side of the hard coat layer 12 opposite to the substrate film 11, and a second side opposite to the first side 12a'. The first side 12a' is a surface that has not been treated with plasma.

[0134] Specifically, in the preparation step, a flexible base film 11 is prepared, and the above-mentioned ultraviolet-curable resin composition is applied to either side of the base film 11 to form a coating film, and then the coating film is cured to form a hard coat layer 12, thereby preparing a base film X' with a hard coat layer.

[0135] The ultraviolet-curable resin composition may contain other components, as necessary, in addition to the ultraviolet-curable resin described above. Examples of the other components include a solvent, a photopolymerization initiator, and a leveling agent.

[0136] The solvent includes, for example, butyl acetate, ethyl acetate, toluene, and cyclopentanone, and preferably includes butyl acetate and cyclopentanone.

[0137] When the ultraviolet-curable resin composition contains a solvent, the coating film on the base film 11 is dried after the ultraviolet-curable resin composition is applied.

[0138] The drying temperature is, for example, 50° C. or more and, for example, 120° C. or less. The drying time is, for example, 10 seconds or more and, for example, 10 minutes or less.

[0139] The coating film on the substrate film 11 is cured by ultraviolet irradiation. Examples of the light source for ultraviolet irradiation include a high-pressure mercury lamp and an LED light. The integrated irradiation amount of ultraviolet light is, for example, 100 mJ / cm. 2 or more, for example, 500 mJ / cm 2 The following is the result.

[0140] In this manner, a long substrate film X' with a hard coat layer is prepared. In this embodiment, a roll of the long substrate film X' with a hard coat layer is prepared. Specifically, the long substrate film X' with a hard coat layer is wound so that the surface of the substrate film X' with a hard coat layer on the hard coat layer side faces inward in the roll radial direction.

[0141] [Device Z] In the manufacturing method of the laminated film Y, the hard-coated substrate film X' is then transported as a workpiece film W by a roll-to-roll method under a reduced pressure atmosphere, and a plasma treatment step and a film-forming step are sequentially performed. Referring to Fig. 5, an apparatus Z, which is an example of an apparatus for performing the plasma treatment step and the film-forming step, will be described. The workpiece film W after the plasma treatment step is the hard-coated film X.

[0142] The apparatus Z includes a payout chamber R1, a winding chamber R2, a connection chamber P1, a plasma processing chamber P2, a connection chamber P3, a film forming chamber P4, a connection chamber P5, a connection chamber P6, and a PEM device (not shown).

[0143] The unwinding chamber R1 is equipped with a unwinding roller 51 for unwinding the workpiece film W. A roll of a long substrate film X' with a hard coat layer is attached to the unwinding roller 51 as the workpiece film W. In addition, a predetermined number of guide rollers G' for guiding the workpiece film W are provided in the unwinding chamber R1.

[0144] The winding chamber R2 is equipped with a winding roller 52 for winding up the workpiece film W. A predetermined number of guide rollers G' for guiding the workpiece film W are provided in the winding chamber R2.

[0145] The connecting chamber P1 is disposed next to the pay-out chamber R1 in the running direction of the workpiece film W, and disposed before the plasma processing chamber P2. A predetermined number of guide rollers G' for guiding the workpiece film W are provided in the connecting chamber P1. The connecting chamber P1 is connected to a vacuum pump (not shown), and is configured so that the pressure inside the connecting chamber P1 can be adjusted. When the device Z is in operation, the pressure inside the connecting chamber P1 is maintained at a predetermined pressure between the pressure inside the pay-out chamber R1 and the pressure inside the plasma processing chamber P2. This ensures a pressure difference between the pay-out chamber R1 and the plasma processing chamber P2.

[0146] The plasma processing chamber P2 is disposed between the connecting chamber P1 and the connecting chamber P3 in the running direction of the workpiece film W. In the plasma processing chamber P2, a plasma processing step is carried out as described below.

[0147] In this embodiment, the plasma processing chamber P2 is equipped with a plurality of low inductance antennas 71. The low inductance antenna means an antenna that has a low inductance of 7.5 μH or less and can generate inductively coupled plasma by applying high frequency power. In this embodiment, the low inductance antenna 71 is supported by a mounting fixture 72 and is covered by a cover block 73 (not shown in FIG. 6) and is disposed inside the plasma processing chamber P2, as shown in FIG. 6 and FIG. 7 (FIG. 6 shows a case where the number of low inductance antennas 71 is four).

[0148] The low inductance antennas 71 are aligned in the travel direction of the workpiece film W and in a direction perpendicular to the travel direction (the width direction of the workpiece film W). The fixture 72 is a vacuum flange. The low inductance antenna 71 is fixed to the fixture 72 via a feedthrough 74 as shown in FIG. 7. The fixture 72 is attached to an opening 75 provided in the wall of the plasma processing chamber P2 as shown in FIG. 5. Specifically, the fixture 72 is attached to the opening 75 with a seal member (not shown) sandwiched between the wall of the plasma processing chamber P2 and the fixture 72. The low inductance antenna 71 is electrically connected to a high frequency power source (RF power source) via an impedance matching device outside the plasma processing chamber P2. Such a low inductance antenna 71 is formed of a conductor. Examples of the conductor include copper and silver, and copper is preferable. The low inductance antenna 71 may be covered with an insulator. Examples of the insulator include glass and quartz.

[0149] The cover block 73 includes a block body 73A and a plurality of partition plates 73B. The block body 73A has a plurality of accommodation spaces 73a. Each accommodation space 73a accommodates one low inductance antenna 71. The partition plates 73B are arranged to close the accommodation spaces 73a. The accommodation spaces 73a are sealed spaces. In the cover block 73, the block body 73A is made of, for example, aluminum. An example of the aluminum is aluminum A5052. The partition plates 73B are made of an insulating material. An example of the insulating material is quartz and glass. The separation distance d' (shown in FIG. 7) between the workpiece film W traveling in the plasma processing chamber P2 and the cover block 73 is, for example, 50 to 200 mm. Such a cover block 73 helps to avoid damage and contamination of the low inductance antenna 71 due to plasma processing without excessively reducing the plasma conversion efficiency due to the power applied to the low inductance antenna 71, and also helps to suppress damage to the work film W (base film X' with a hard coat layer) being plasma processed.

[0150] The plasma processing chamber P2 may further include a transport roller 53. The transport roller 53 is a main guide roller for transporting the workpiece film W in the plasma processing chamber P2. The transport roller 53 has a temperature adjustment function that can heat or cool the workpiece film W. That is, the transport roller 53 is a roller with a temperature adjustment function. When the device Z is in operation, the transport roller 53 transports the hard-coat-layer-attached base film X' while contacting the second surface of the hard-coat-layer-attached base film X'. The low-inductance antenna 71 is disposed opposite the transport roller 53. When the transport roller 53 is provided, in the plasma processing step described later, the hard-coat-layer-attached base film X' is transported while being cooled or heated by a roller (transport roller 53) with a temperature adjustment function that contacts the hard-coat-layer-attached base film X' in the plasma processing chamber P2 (chamber), and plasma processing is performed on the hard-coat-layer-attached base film X'. By controlling the temperature of the base film X' having a hard coat layer, the thermal deformation of the workpiece film W can be suppressed, and the influence of the thermal deformation on the transport of the workpiece film W can also be suppressed.

[0151] As shown in FIG. 6, the low inductance antenna 71 has an open loop shape in this embodiment. The open loop shape of the low inductance antenna 71 is advantageous in lowering the inductance of the low inductance antenna 71. Therefore, the open loop shape of the low inductance antenna 71 can suppress an increase in voltage due to an increase in the power applied to the low inductance antenna 71. This can suppress abnormal discharge during plasma processing, which will be described later. By suppressing abnormal discharge, damage to the workpiece film W (base film X' with hard coat layer) to be plasma processed can be suppressed. Specifically, the low inductance antenna 71 has a U-shape having two free ends. For each low inductance antenna 71, the two free ends are fixed to the mounting fixture 72 so as to be aligned in the width direction of the workpiece film W. In addition, in this embodiment, the low inductance antenna 71 has an extension portion 71a on the opposite side to the two free ends. The extension portion 71a extends parallel to the workpiece film W passing through the plasma processing chamber P2. Each extension portion 71a extends in the width direction of the workpiece film W. Each extension portion 71a may extend in the running direction of the workpiece film W (four low inductance antennas 71 may be arranged in this manner). The length of the extension portion 71a is, for example, 50 to 150 mm (FIG. 6 shows a case where the length of the extension portion 71a is the same as the maximum length d2 of the low inductance antenna 71 described below). The low inductance antenna 71 may have a coil shape instead of an open loop shape.

[0152] The low inductance antenna 71 extends from the fixture 72 toward the workpiece film W. The low inductance antenna 71 preferably extends perpendicularly to the fixture 72. The extension length d1 of the low inductance antenna 71 from the fixture 72 is, for example, 30 to 150 mm. The maximum length d2 of the low inductance antenna 71 in the surface direction of the workpiece film W is, for example, 50 to 200 mm. The separation distance d3 (shown in FIG. 7) between the low inductance antenna 71 and the workpiece film W is, for example, 50 to 200 mm. The extension length d1 and the separation distance d3 are preferably the same. The ratio (d3 / d1) of the separation distance d3 to the extension length d1 is, for example, 0.5 to 3.5. The number (number of rows) of the low inductance antennas 71 arranged at a distance in the traveling direction of the workpiece film W may be 1, 2, or 3 depending on the traveling speed (i.e., plasma processing time) of the workpiece film W, or may be 4 or more if necessary. In the traveling direction of the workpiece film W, the center-to-center distance d4 between adjacent low inductance antennas 71 is, for example, 100 to 500 mm. In the width direction of the workpiece film W, the center-to-center distance d5 between adjacent low inductance antennas 71 is, for example, 200 to 500 mm. By adjusting the center-to-center distance d5, the uniformity of the plasma density in the width direction of the workpiece film W, which will be described later, can be controlled. The center-to-center distance d4 and the center-to-center distance d5 are preferably the same. The ratio (d5 / d4) of the center-to-center distance d5 to the center-to-center distance d4 is, for example, 0.5 to 2.0. The centers of the extensions 71a of the four low inductance antennas 71 preferably form a square with the vertices as vertices. High density plasma can be generated by such a pair of low inductance antennas 71. As the low inductance antenna 71, for example, a high frequency antenna for generating plasma described in JP 2013-258153 A may be used.

[0153] The PEM device is a device for performing plasma emission monitoring (PEM) during plasma processing, and includes a device body and an optical fiber for collecting light. The tip (one end) of the optical fiber is disposed between the workpiece film W and the low inductance antenna 71 in the plasma processing chamber P2. The other end of the optical fiber is connected to the device body. In addition, a first line L1 equipped with a flow rate control valve for introducing gas into the chamber is connected to the plasma processing chamber P2.

[0154] The connecting chamber P3 is disposed next to the plasma processing chamber P2 in the running direction of the workpiece film W and disposed before the film forming chamber P4. A predetermined number of guide rollers G' for guiding the workpiece film W are provided in the connecting chamber P3. The connecting chamber P3 is connected to a vacuum pump (not shown) and is configured to be able to adjust the pressure inside the chamber. When the device Z is in operation, the pressure inside the connecting chamber P3 is maintained at a predetermined pressure between the pressure inside the plasma processing chamber P2 and the pressure inside the film forming chamber P4. This ensures a pressure difference between the plasma processing chamber P2 and the film forming chamber P4.

[0155] The film-forming chamber P4 is disposed next to the connection chamber P3 in the running direction of the workpiece film W. The film-forming chamber P4 is connected to a vacuum pump (not shown) and is configured to be able to adjust the interior of the chamber to a predetermined vacuum level. In the film-forming chamber P4, a film-forming process is carried out as described below.

[0156] In this embodiment, the film forming chamber P4 is a sputtering film forming chamber. The film forming chamber P4 includes a film forming roller 54 and a plurality of sputtering chambers 60 (sputtering chambers 60a to 60e) (a case where the number of sputtering chambers 60 is 5 is illustrated as an example). The film forming roller 54 is a main guide roller for transporting the workpiece film W in the film forming chamber P4. The film forming roller 54 has a temperature adjustment function capable of heating or cooling the workpiece film W. The sputtering chamber 60 is a space partitioned in the film forming chamber P4. The plurality of sputtering chambers 60 are arranged along the circumferential direction of the film forming roller 54. Each sputtering chamber 60 opens toward the film forming roller 54. A cathode 61 is provided in the sputtering chamber 60. A target (not shown) is arranged on the cathode 61 as a film forming material supply material. The target is arranged on the target so as to face the film forming roller 54. Each sputtering chamber 60 is provided with a power supply (not shown) for applying a voltage to the target to generate a glow discharge. Examples of power supplies include a DP power supply, an AC power supply, an MF power supply, an RF power supply, and an MF-AC power supply. An MF-AC power supply refers to an AC power supply with a frequency band of several kHz to several MHz. A required number of second lines (not shown) equipped with flow rate control valves for introducing gas into the chamber are connected to each sputtering chamber 60. A predetermined number of guide rollers G' for guiding the workpiece film W are provided in the film formation chamber P4.

[0157] The connecting chamber P5 and the connecting chamber P6 are arranged in this order between the film forming chamber P4 and the winding chamber R2 in the running direction of the workpiece film W. A predetermined number of guide rollers G' for guiding the workpiece film W are provided in the connecting chamber P5. A predetermined number of guide rollers G' for guiding the workpiece film W are provided in the connecting chamber P6. The connecting chamber P5 is connected to a vacuum pump (not shown) and is configured to be able to adjust the pressure inside the connecting chamber P5. The connecting chamber P6 is connected to a vacuum pump (not shown) and is configured to be able to adjust the pressure inside the connecting chamber P5. When the device Z is in operation, the pressure inside the connecting chambers P5 and P6 is maintained at a predetermined pressure between the pressure inside the film forming chamber P4 and the pressure inside the winding chamber R2. This ensures a pressure difference between the film forming chamber P4 and the winding chamber R2.

[0158] A plasma processing step and a film forming step are sequentially performed by the above-described apparatus Z. Specifically, the steps are as follows.

[0159] (Plasma treatment process) The workpiece film W is unwound from the unwinding chamber R1. After being unwound from the unwinding chamber R1, the workpiece film W passes through the connecting chamber P1, the plasma processing chamber P2, the connecting chamber P3, the film forming chamber P4, the connecting chamber P5, and the connecting chamber P6 in sequence, and is wound up in the winding chamber R2. The running speed of the workpiece film W is, for example, 0.1 m / min or more, preferably 0.5 m / min or more, more preferably 0.7 m / min or more, and even more preferably 0.9 m / min or more, and is, for example, 10 m / min or less, preferably 8 m / min or less, and more preferably 5 m / min or less. In addition, the series of lines from the unwinding chamber R1 to the winding chamber R2 are not open to the atmosphere along the way, and the process is carried out in the line under a reduced pressure atmosphere. The reduced pressure atmosphere is preferably under vacuum. Under vacuum preferably means a reduced pressure atmosphere of 7 Pa or less.

[0160] In the plasma treatment chamber P2, a plasma treatment process is carried out. In the plasma treatment process, in a reduced pressure atmosphere in the plasma treatment chamber P2 (chamber), the first surface 12a' of the workpiece film W (substrate film X' with a hard coat layer) is plasma-treated while detecting the plasma emission intensity. In this embodiment, the plasma treatment is a treatment by inductively coupled plasma of an oxygen-containing gas (oxygen-plasma treatment) generated by applying high-frequency power to the low-inductance antenna (low-inductance antenna) 71. Specifically, it is as follows.

[0161] Oxygen is supplied into the plasma processing chamber P2 during plasma processing through the first line L1. In addition to oxygen, an inert gas may be supplied into the plasma processing chamber P2. Examples of the inert gas include argon, krypton, and xenon. The gas in the plasma processing chamber P2 may contain other gases other than the inert gas and oxygen. Examples of the other gases include nitrogen and hydrogen. The oxygen concentration of the gas (oxygen-containing gas) in the plasma processing chamber P2 is, for example, 30 volume % or more, preferably 50 volume % or more, more preferably 80 volume % or more, even more preferably 90 volume % or more, particularly preferably 95 volume % or more, and most preferably 100 volume %. If the oxygen concentration is equal to or higher than the lower limit, high-density oxygen plasma can be generated. This has an effect on the nanometer-order fine unevenness of the first surface 12a' of the workpiece film W (base film X' with a hard coat layer) and the change in chemical bonds near the surface of the first surface 12a' of the workpiece film W (base film X' with a hard coat layer).

[0162] The pressure (first pressure) in the plasma processing chamber P2 during plasma processing is, for example, 0.1 Pa or more, preferably 0.2 Pa or more, more preferably 0.3 Pa or more, and for example, 7 Pa or less, preferably 5 Pa or less, more preferably 3 Pa or less. If the first pressure is equal to or greater than the above-mentioned lower limit, a plasma environment of sufficient density for surface modification processing of the workpiece film W can be formed in the plasma processing chamber P2 in the plasma processing. If the first pressure is equal to or less than the above-mentioned upper limit, damage to the workpiece film W caused by excessively high-density plasma can be suppressed in the plasma processing. The first pressure can be adjusted by the amount of oxygen gas supplied into the plasma processing chamber P2.

[0163] The frequency of the high frequency power applied to the low inductance antenna 71 during plasma processing is, for example, 1 MHz or more, preferably 5 MHz or more, more preferably 10 MHz or more, and for example, 100 MHz or less, preferably 80 MHz or less, more preferably 60 MHz or less. If the frequency of the high frequency power is equal to or higher than the lower limit, the plasma discharge can be stabilized while increasing the plasma current density in the plasma processing. If the frequency of the high frequency power is equal to or lower than the upper limit, the antenna potential can be suppressed, and therefore damage to the workpiece film W caused by the plasma can be suppressed. In addition, the high frequency power is, for example, 0.1 kW or more, preferably 0.3 kW or more, more preferably 1.0 kW or more, and for example, 10 kW or less, preferably 8 kW or less, more preferably 6 kW or less. If the high frequency power is equal to or higher than the lower limit, a high density plasma environment can be formed in the plasma processing chamber P2 in the plasma processing by inductively coupled plasma. If the high frequency power is equal to or lower than the upper limit, excessive damage to the workpiece film W caused by the plasma can be suppressed.

[0164] In the plasma treatment step, the plasma emission intensity during the plasma treatment is preferably monitored by a PEM device, and the amount of oxygen gas introduced, the high frequency power, the travel speed, and the like are controlled based on the monitoring results.

[0165] In the plasma treatment process, the plasma current density at the intermediate position between the low inductance antenna 71 and the workpiece film W (the substrate film X' with a hard coat layer) is, for example, 1.0 mA / Pm 3 More than 2.0mA / Pm 3 More preferably, 3.0mA / Pm 3 or more, for example, 10mA / Pm 3 Less than 8mA / Pm, preferably 3 Less than or equal to 4mA / Pm 3 The following is the results. Inductive coupling type plasma processing using a low inductance antenna can achieve a higher plasma current density (for example, a plasma density about 100 times higher) than the above-mentioned capacitive coupling type plasma processing. If the plasma current density is equal to or higher than the above-mentioned lower limit, sufficient plasma oxygen particles can be secured in the plasma processing chamber P2 during plasma processing, and the surface of the workpiece film W can be appropriately modified. If the plasma current density is equal to or lower than the above-mentioned upper limit, damage to the workpiece film W caused by excessively high density plasma oxygen particles can be suppressed during plasma processing. Methods for adjusting the plasma current density include, for example, adjusting the amount of oxygen gas introduced into the plasma processing chamber P2, adjusting the frequency of the high frequency power applied to the high frequency power source, and adjusting the magnitude of the applied power.

[0166] By subjecting the substrate film X' with a hard coat layer to the above-mentioned plasma treatment, a hard coat film X having a hard coat layer 12 is produced as shown in Fig. 4B. By not carrying out the next film-forming step, a hard coat film X in which no inorganic layer 20 is formed on the hard coat layer 12 is obtained.

[0167] (Film forming process) In the film forming step, following the plasma treatment step, an inorganic layer 20 is formed on the hard coat layer 12 (on the first surface 12a) of the workpiece film W (hard coat film X) after the plasma treatment step by sputtering, deposition or chemical vapor deposition in a reduced pressure atmosphere. In the film forming step, the inorganic layer 20 is preferably formed by sputtering. The reduced pressure atmosphere is preferably a vacuum.

[0168] In the sputtering method, a sputtering gas (inert gas) is introduced into each sputtering chamber 60 through one second line, while a negative voltage is applied to a target (film forming material) arranged on a cathode 61 in the sputtering chamber 60. This generates a glow discharge to ionize gas atoms, and the gas ions collide with the target surface at high speed, ejecting the target material from the target surface, and the ejected target material is deposited on the workpiece film W. Examples of sputtering gases include argon, krypton, and xenon.

[0169] When the deposition material is a metal oxide, the sputtering method may be a reactive sputtering method. In the reactive sputtering method, oxygen (reactive gas) is introduced into the sputtering chamber 60 in addition to the sputtering gas. The oxygen is introduced into the sputtering chamber 60 through another second line. In the reactive sputtering method, the target is made of, for example, a metal in the metal oxide that forms each layer.

[0170] In the sputtering method, the pressure (second pressure) in the sputtering chamber 60 is, for example, 0.1 to 5.0 Pa depending on the type of layer to be formed. The film formation temperature (the temperature of the workpiece film W adjusted by the film formation roller 54) is, for example, -10°C to 150°C.

[0171] In the film forming step, next, an inorganic layer 20 is formed on the hard coat layer 12 (on the first surface 12a) by a sputtering method in at least one sputtering chamber selected from the sputtering chambers 60a to 60e. For example, at least one selected from an adhesive layer, an anti-reflection layer, and a conductive layer is formed as the inorganic layer 20. More specifically, when manufacturing the laminated film Y shown in FIG. 3, an adhesive layer 21 is formed on the hard coat layer 12 in the sputtering chamber 60a, a high refractive index layer 22a is formed on the adhesive layer 21 in the sputtering chamber 60b, a low refractive index layer 22b is formed on the high refractive index layer 22a in the sputtering chamber 60c, a high refractive index layer 22c is formed on the low refractive index layer 22b in the sputtering chamber 60d, and a low refractive index layer 22d is formed on the high refractive index layer 22c in the sputtering chamber 60e.

[0172] In the device Z, after the plasma treatment process and the film forming process, the laminated film Y as the workpiece film W passes through the connecting chambers P5 and P6 and reaches the winding chamber R2, where it is wound up by the winding roller 52.

[0173] In this manner, a long laminate film Y is produced. EXAMPLES

[0174] The present invention will be described in more detail below with reference to examples and comparative examples. The present invention is not limited to the examples and comparative examples. The specific numerical values ​​of the blending ratio (content ratio), physical property values, parameters, etc. used in the following description can be replaced with the upper limit (a numerical value defined as "not more than" or "less than") or lower limit (a numerical value defined as "not less than" or "exceeding") of the corresponding blending ratio (content ratio), physical property values, parameters, etc. described in the above "Form for carrying out the invention".

[0175] Example 1 <Production of substrate film with hard coat layer> First, a hard coat layer was formed on one side of a triacetyl cellulose (TAC) film as a base film. Specifically, 100 parts by mass (solid content equivalent value) of a butyl acetate solution of an ultraviolet-curable acrylic urethane resin (product name "Luxidia 17-806", solid content concentration 80% by mass, manufactured by DIC Corporation), 5 parts by mass of a photopolymerization initiator (product name "Omnirad907", manufactured by IGM Resins), 0.03 parts by mass of a leveling agent (product name "GRANDIC PC4100", manufactured by DIC Corporation), and butyl acetate as a solvent were mixed to prepare a first resin composition with a solid content concentration of 75% by mass. Next, cyclopentanone was further added as a solvent to the first resin composition to prepare a second resin composition with a solid content concentration of 50% by mass. Meanwhile, a long TAC film (length 100 m, width 340 mm, thickness 40 μm) was prepared. Next, the second resin composition was applied to one side of the TAC film to form a coating film. This coating film was dried by heating and then cured by ultraviolet irradiation. As a result, a hard coat layer having a thickness of 5 μm was formed on the TAC film. The drying conditions were a heating temperature of 100° C. and a heating time of 60 seconds. For ultraviolet irradiation, a high-pressure mercury lamp was used as a light source, and ultraviolet rays with a wavelength of 365 nm were irradiated onto the coating film, with an integrated irradiation amount of 300 mJ / cm. 2 In this manner, a roll of the substrate film with a hard coat layer (hard coat film before plasma treatment) was produced. In the substrate film with a hard coat layer, the surface of the hard coat layer opposite to the TAC film was a plasma untreated surface.

[0176] <Manufacture of hard coat film> While the substrate film with a hard coat layer was transported by a roll-to-roll system under vacuum, a plasma treatment was carried out on the surface of the hard coat layer of the substrate film with a hard coat opposite to the TAC film (plasma untreated surface).

[0177] For the plasma treatment, an apparatus (first apparatus) capable of performing a roll-to-roll process on the work film was used. The first apparatus includes a payout chamber, a plasma treatment chamber, a film formation chamber, and a winding chamber. The payout chamber, the plasma treatment chamber (first plasma treatment chamber), the film formation chamber, and the winding chamber are arranged in this order, and are further connected to each other. The payout chamber includes a payout roller. A roll of the above-mentioned hard-coated base film was set on the payout roller as the work film. The plasma treatment chamber includes a transport roller with a temperature control function (transport roller 53 in FIG. 5) and four low inductance antennas (low inductance antennas 71 in FIG. 6 and FIG. 7) covered with a cover block (cover block 73 in FIG. 7) as shown in FIG. 6 and FIG. 7. Each low inductance antenna has an extension portion (extension portion 71a in FIG. 6) parallel to the base film. In the four low inductance antennas, the extension length d1 is 88 mm, the maximum length d2 (length of the extension portion) is 100 mm, the separation distance d3 is 112 mm, the center distance d4 is 290 mm, and the center distance d5 is 280 mm (FIGS. 6 and 7). Each low inductance antenna is electrically connected to a high frequency power source (RF power source, frequency 13.56 MHz) via an impedance matching device outside the plasma processing chamber. The separation distance d' between the base film traveling in the plasma processing chamber and the cover block is 100 mm. The film formation chamber is a sputtering film formation chamber, and includes a film formation roller and a cathode arranged opposite the film formation roller. The winding chamber includes a winding roller.

[0178] Using the above-mentioned first device, specifically, while the hard-coated substrate film was transported from the unwinding chamber to the winding chamber in a roll-to-roll manner, the surface of the hard-coated substrate film opposite the TAC film was plasma-treated in the plasma treatment chamber. The running speed of the hard-coated substrate film (film running speed) was 1.3 m / min. The temperature of the temperature-adjustable transport roller was -8°C. The plasma treatment conditions were as follows.

[0179] The ultimate vacuum level of the plasma processing chamber is 1.0×10 -4 After evacuating the inside of the apparatus until the pressure reached 0.5 Pa, oxygen gas was introduced into the plasma treatment chamber, and the pressure in the plasma treatment chamber was set to 0.5 Pa. By applying high frequency power of 5.0 kW to the four low inductance antennas by a high frequency power source, an inductively coupled plasma of an oxygen-containing gas was formed around the four low inductance antennas (the surface of the hard coat layer of the hard coat-coated substrate film opposite the TAC film (the plasma untreated surface) was plasma-treated by this plasma).

[0180] In the above manner, the hard coat film of Example 1 was produced. The hard coat film of Example 1 includes a substrate film and a hard coat layer on one side of the substrate film. In the hard coat film of Example 1, the surface of the hard coat layer opposite the TAC film is plasma-treated. In other words, the hard coat film of Example 1 has a plasma-treated surface. This plasma treatment is a treatment by inductively coupled plasma using an oxygen-containing gas generated by application of high-frequency power to a low-inductance antenna (oxygen-plasma treatment).

[0181] Comparative Example 1 A hard coat layer was formed on one surface of the TAC film in the same manner as in Example 1. In this way, a roll of a substrate film with a hard coat layer (hard coat film before plasma treatment) was obtained.

[0182] Next, while the substrate film with the hard coat layer was transported by a roll-to-roll system under vacuum, a plasma treatment was performed on the surface of the hard coat layer of the substrate film with the hard coat layer opposite to the TAC film (plasma untreated surface).

[0183] For the plasma treatment, a second device capable of performing a roll-to-roll process on the work film was used. The second device has the same configuration as the first device, except that the second plasma treatment chamber is provided instead of the first plasma treatment chamber. The second plasma treatment chamber is provided with a cathode electrode and an anode electrode (both rectangular electrodes made of SUS304) as a pair of flat electrodes for generating plasma. The pair of flat electrodes are arranged parallel to the substrate film with a hard coat layer passing through the second plasma treatment chamber with a 50 mm gap between them. The anode electrode is arranged at a position 35 mm away from the substrate film with a hard coat layer passing through the second plasma treatment chamber, and is grounded outside the second plasma treatment chamber. The cathode electrode is arranged so as to face the surface of the substrate film with a hard coat layer on the opposite side to the TAC film, and is electrically connected to a high-frequency power source (RF power source, 13.56 MHz) via an impedance matching device. The length of each electrode facing the substrate film with a hard coat layer in the film running direction is 110 mm, and the length in the width direction is 430 mm.

[0184] Using the above-mentioned second device, specifically, while the hard coat film was transported from the unwinding chamber to the winding chamber in a roll-to-roll manner, the surface of the hard coat layer of the substrate film with the hard coat layer opposite the TAC film was plasma treated in the second plasma treatment chamber (bombardment treatment). The running speed of the substrate film with the hard coat layer (film running speed) was 1.0 m / min. The conditions of the plasma treatment were as follows.

[0185] The ultimate vacuum in the second plasma processing chamber is 1.0×10 -4 After evacuating the inside of the apparatus until the pressure reached 1.0 Pa, argon was introduced into the second plasma treatment chamber, and the pressure in the plasma treatment chamber was set to 1.0 Pa. Capacitively coupled plasma (CCP) was generated by applying a power of 300 W between the planar electrodes by a high-frequency power source. In this plasma environment, a bombardment treatment (BB treatment) with argon ions was performed on the surface of the hard coat layer of the substrate film with a hard coat layer opposite the TAC film.

[0186] In this manner, the hard coat film of Comparative Example 1 was produced. In the hard coat film of Comparative Example 1, the surface of the hard coat layer opposite to the TAC film was plasma treated. In other words, the hard coat film of Example 1 has a plasma-treated surface. This plasma treatment is an ion bombardment treatment (BB treatment) by capacitively coupled plasma using argon gas.

[0187] Example 2 <Manufacturing of laminated film> Similarly to Example 1, a hard coat film was produced, and an inorganic layer was formed on the hard coat film continuously after oxygen plasma treatment to produce a laminated film. Specifically, a 5 nm thick indium tin oxide (ITO) layer was formed as an inorganic layer on one side of the hard coat layer of the hard coat film (the side of the hard coat layer opposite to the TAC film) by an apparatus equipped with a sputtering film-forming chamber capable of sputtering film-forming by a roll-to-roll method, to produce a laminated film. The sputtering film-forming chamber is equipped with a film-forming roller (film-forming roller 54 in FIG. 5) and a sputtering chamber (sputtering chamber 60a in FIG. 5). The sputtering chamber is a space partitioned within the film-forming chamber. The sputtering chamber is equipped with a cathode arranged opposite the film-forming roller. The sputtering chamber is connected to a required number of second lines (not shown) equipped with flow rate control valves for introducing gas into the chamber.

[0188] In the sputtering deposition chamber, an ITO layer with a thickness of 5 nm was deposited as an inorganic layer by reactive sputtering. Specifically, an ITO target (tin oxide concentration 10 mass%, 600 mm long x 150 mm wide x 5 mm thick, single cathode type) was first installed in the sputtering deposition chamber. The ultimate vacuum in the deposition chamber of the device was 1.0 x 10 -4After evacuation to 100 Pa, argon gas as an inert gas and oxygen gas as a reactive gas, 5 parts by volume per 100 parts by volume of argon gas, were introduced into the sputtering deposition chamber, and the pressure in the deposition chamber (deposition pressure) was set to 0.4 Pa. Furthermore, a DC power supply was used as the power supply for applying voltage to the target, and the discharge power was set to 0.8 kW. The deposition temperature (temperature of the deposition roll) was set to -8°C.

[0189] In this manner, a laminate film of Example 2 was produced. The laminate film of Example 2 had an ITO layer on one side of the hard coat layer of the hard coat film of Example 1 (the side of the hard coat layer opposite the TAC film).

[0190] Comparative Example 2 A hard coat film was produced in the same manner as in Comparative Example 1, and an inorganic layer was formed on the hard coat film continuously after the BB treatment to produce a laminated film. The inorganic layer was formed in the same manner as in Example 2.

[0191] In this manner, a laminated film of Comparative Example 2 was produced. The laminated film of Comparative Example 2 had an ITO layer on one side of the hard coat layer in the hard coat film of Comparative Example 1 (the side of the hard coat layer opposite the TAC film).

[0192] <Evaluation> [Chemical bond state] Fourier transform infrared spectrophotometer analysis (FT-IR analysis) was carried out according to the following procedure.

[0193] (FT-IR analysis) 1. The substrate film with a hard coat layer used in each Example and Comparative Example, the hard coat films of Example 1 and Comparative Example 1, and the laminate films of Example 2 and Comparative Example 2 were prepared. 2. In the substrate film with the hard coat layer used in each Example and Comparative Example, the infrared absorption spectrum of the substrate film with the hard coat layer was measured from the plasma untreated surface side by the total reflection measurement method (ATR method) using a Fourier transform infrared spectrophotometer (FT-IR) (Nicolet 6700 / Thunderdome, manufactured by Thermo Fisher Scientific Co., Ltd.), the hard coat film of Example 1 and Comparative Example 1 was measured from the plasma treated surface side by the total reflection measurement method (ATR method) using a Fourier transform infrared spectrophotometer (FT-IR), and the laminate film of Example 2 and Comparative Example 2 was measured from the surface side of the ITO layer by the total reflection measurement method (ATR method) using a Fourier transform infrared spectrophotometer (FT-IR). The measurement was performed once, and Ge crystal was used. The measurement conditions were as follows. {Measurement conditions} Incident angle: 45° Resolution: 4cm -1 Measurement range: 4000-675cm -1 Detector: DTGS 3. The absorbance ratios of the following A to J were calculated from the infrared absorption spectra of the substrate film with a hard coat layer, the hard coat film, and the laminate film. Note that the following A to J include both the above-mentioned A1 to J1 and A2 to J2.

[0194] A: Wave number of 2960 cm due to CH groups in hard coat film and laminated film -1 Absorbance at 2960 ) for the C=C group at 1635 cm -1 Absorbance at 1635 ) ratio (A=Ab 1635 / Ab 2960 ) B: The ratio of absorbance at the same wavenumber as A in the substrate film with the hard coat layer (B = Ab 1635 ' / Ab 2960 ') C: Wavenumber of 2960 cm due to CH groups in the hard coat film and laminated film -1 Absorbance at 2960 ) for the C=O group at 1725 cm -1 Absorbance at 1725 ) ratio (C=Ab 1725 / Ab 2960 ) D: The ratio of absorbance at the same wavenumber as C in the substrate film with the hard coat layer (D = Ab 1725 ' / Ab 2960 ') E: Wavenumber of 2960 cm due to CH groups in the hard coat film and laminated film -1 Absorbance at 2960 ) with a wavenumber of 1524 cm due to the NH group -1 Absorbance at 1524 ) ratio (E=Ab 1524 / Ab 2960 ) F: The ratio of absorbance at the same wavenumber as E in the substrate film with the hard coat layer (F = Ab 1524 ' / Ab 2960 ') G: Wavenumber 2960 cm due to CH groups in hard coat film and laminated film -1 Absorbance at 2960 ) for the C=C group at 810 cm -1 Absorbance at 810 ) ratio (G=Ab 810 / Ab 2960 ) H: The ratio of absorbance at the same wavenumber as G in the substrate film with the hard coat layer (H = Ab 810 ' / Ab 2960 ') I: Wavenumber 2960 cm due to CH groups in hard coat film and laminated film -1 Absorbance at 2960 ) with a wave number of 1159 cm due to the CO group -1 Absorbance at 1159 ) ratio (I=Ab 1159 / Ab 2960 ) J: The ratio of absorbance at the same wavenumber as I in the substrate film with the hard coat layer (J = Ab 1159 ' / Ab 2960 ')

[0195] Note that each of the wave numbers listed above in A to J is a wave number indicating the peak position due to the corresponding chemical bond, and may vary slightly. Also, some deviation may occur due to measurement fluctuations. Therefore, each of the wave numbers listed above is within the range of ±10 cm. -1 A degree of deviation is permitted.

[0196] The above-mentioned substrate film with hard coat layer, hard coat film, and laminated film were measured with a Fourier transform infrared spectrophotometer, and the following (1) to (5) were calculated using the calculated absorbance ratios (A to J). The results are shown in Table 1. The following (1) to (5) quantitatively indicate the extent to which the state of chemical bonds in the substrate film with hard coat layer changed after plasma treatment and lamination of an ITO layer, and show the amount of change when the state of chemical bonds in the substrate film with hard coat layer is taken as 100%. In other words, the closer the following (1) to (5) are to 100%, the more the changes in the hard coat film and laminated film can be suppressed relative to the substrate film with hard coat layer, while the larger the difference from 100%, the less the changes in the hard coat film and laminated film can be suppressed relative to the substrate film with hard coat layer.

[0197] (1) A / B (2) C / D (3) E / F (4) G / H (5) I / J

[0198] [Surface roughness] The surface roughness of the hard coat layer surface was examined for the hard coat films of Example 1 and Comparative Example 1. Specifically, first, the exposed surface of the hard coat layer in the hard coat film was observed and imaged using an atomic force microscope (Dimention Edge SPC-160113-01, manufactured by Bruker). In the observation, the measurement mode was set to tapping mode, and an antimony-doped Si cantilever (RTESP-300, manufactured by Bruker) was used as a probe. Next, the surface roughness (arithmetic mean height based on ISO 25178-2:2012) Sa of the hard coat layer surface was obtained from the observation image of 1 μm square. The results are shown in Table 1.

[0199] [Optical properties] The transmittance of the hard coat films of Example 1 and Comparative Example 1 was measured using an ultraviolet-visible-infrared spectrophotometer (U4150, manufactured by Hitachi High-Tech Science Corporation). Based on the measured values ​​of the transmittance at each wavelength from 380 nm to 780 nm, the color value (b*) was calculated using a color calculation program (Hitachi spectrophotometer dedicated software, program included) and evaluated according to the following criteria. The results are shown in Table 1. The color value (b*') of the substrate film with the hard coat layer used in each Example and Comparative Example was 0.54.

[0200] {standard} ○: -0.6≦b*≦0.6, or |b*-b*'|≦0.1 ×: -0.6>b* or 0.6<b*、かつ、|b*-b*’|> 0.1

[0201] [Adhesion] The adhesion of the laminated films of Example 2 and Comparative Example 2 was evaluated according to the following criteria by carrying out the following First and Second Tests. The results are shown in Table 1.

[0202] Test 1: First, the exposed surface of the substrate film in the laminated film was fixed to a glass plate. Next, the inorganic layer of the laminated film on the glass plate was irradiated with light from a metal halide lamp for 32.5 hours using a weather resistance tester (Eye Super UV Tester SUV-W161, manufactured by Iwasaki Electric Co., Ltd.) (accelerated weather resistance test). Other conditions included a temperature of 85°C, a relative humidity of 45%, and an irradiation intensity (290-450 nm integrated illuminance) of 150mW / cm. 2 It was decided.

[0203] Test 2: First, eleven parallel first incisions (1 mm apart) extending linearly in a first direction and eleven parallel second incisions (1 mm apart) extending linearly in a second direction perpendicular to the first direction were made with a cutter knife on the inorganic layer of the laminated film on the glass plate after the first test, and 100 grids were formed by the first and second incisions. Next, a polyester wiper (Anticon Gold, manufactured by Sanplatec Co., Ltd.) was slid over the 100 grid areas of the laminated film while continuously dripping isopropyl alcohol at 2 mL / min. The sliding conditions were a wiper contact surface of 20 mm x 20 mm, a load of 1.5 kg / 20 mm, and 1000 reciprocations. Next, 1 mm of the 100 grids were removed. 2 The number of squares in which the above peeling occurred was counted, and the counted number was divided by 100 to calculate the peeling rate (%).

[0204] {standard} ○: Peeling rate is 5% or less ×: Peeling rate exceeds 5%

[0205] [Table 1]

[0206] [Consideration] In the hard coat film of Comparative Example 1, A / B≦72%, C / D≦46%, E / F≧155%, G / H≦50%, and I / J≦50%. In other words, it was suggested that in Comparative Example 1, the change in the state of chemical bonds due to the bombardment treatment (BB treatment) could not be suppressed inside the hard coat film. In addition, the hard coat film of Comparative Example 1 has inferior optical properties compared to the substrate film with the hard coat layer before the plasma treatment. In other words, it was suggested that the bombardment treatment (BB treatment) causes great damage to the hard coat film.

[0207] On the other hand, in the hard coat film of Example 1, A / B>50%, C / D>72%, E / F<155%, G / H>50%, and I / J>50%. In other words, it was suggested that in Example 1, the change in the state of chemical bonds inside the hard coat film due to the treatment by inductively coupled plasma using an oxygen-containing gas (oxygen-plasma treatment) was suppressed. In addition, in the hard coat film of Example 1, there was almost no change in the optical properties from the substrate film with the hard coat layer before the plasma treatment. In other words, it was suggested that the treatment by inductively coupled plasma using an oxygen-containing gas (oxygen-plasma treatment) caused little damage to the hard coat film.

[0208] In addition, the hard coat film of Comparative Example 1 does not contain particles such as silica particles in the hard coat layer, so the surface of the hard coat layer does not have unevenness caused by particles. The surface of the hard coat layer of Comparative Example 1 opposite to the TAC film is bombarded (BB treated). The surface roughness Sa of the hard coat layer of such a hard coat film of Comparative Example 1 is 0.78, which is less than 0.80. In Comparative Example 2 in which an inorganic layer is laminated on the hard coat film of Comparative Example 1, as described above, Comparative Example 1 does not have sufficient surface roughness (is not roughened), so the adhesion of the inorganic layer could not be ensured.

[0209] On the other hand, in the hard coat film of Example 1, the hard coat layer does not contain particles such as silica particles, so the surface of the hard coat layer does not have unevenness caused by particles. The surface of the hard coat layer of Example 1 opposite to the TAC film is treated with inductively coupled plasma using an oxygen-containing gas (oxygen-plasma treatment). The surface roughness Sa of the hard coat layer of such a hard coat film of Example 1 is 1.30, which is significantly greater than 0.80. In Example 2, in which an inorganic layer is laminated on the hard coat film of Example 1, as described above, Example 1 has sufficient surface roughness (is roughened), so the adhesion of the inorganic layer can be ensured. [Explanation of symbols]

[0210] X Hard Coat Film Y laminated film H' thickness direction D' plane direction 11 Base film 12 Hard coat layer 12a Plasma-treated surface 20 Inorganic layer 21 Adhesion layer 22a, 22c High refractive index layer 22b, 22d Low refractive index layer

Claims

1. A hard coat film comprising a flexible base film and a hard coat layer disposed on at least one surface of the base film, the hard coat layer contains a cured product of an acrylic urethane resin, the surface of the hard coat layer opposite to the substrate film is a plasma-treated surface; The surface roughness Sa of the plasma-treated surface is 0.8 nm or more and 4.5 nm or less; A hard coat film, in which a ratio of absorbances calculated by the following Fourier transform infrared spectrophotometer analysis (FT-IR analysis) satisfies at least one of the following relationships (1) and (2): (1) A / B>72% (2) C / D>46% (FT-IR analysis) 1. The hard coat film and a substrate film with a hard coat layer, which is the hard coat film before plasma treatment (in the substrate film with a hard coat layer, the surface of the hard coat layer opposite to the substrate film is a plasma untreated surface), are prepared.

2. The infrared absorption spectrum of the hard coat film is measured from the plasma-treated surface side by a total reflection measurement method using a Fourier transform infrared spectrophotometer (FT-IR), and the infrared absorption spectrum of the substrate film with the hard coat layer is measured from the plasma-untreated surface side by a total reflection measurement method using a Fourier transform infrared spectrophotometer (FT-IR).

3. The ratio of absorbance A to D below for the hard coat film and the substrate film with the hard coat layer is calculated from the infrared absorption spectrum. A: Wave number of 2960 cm due to C—H groups in the hard coat film -1 Absorbance at 2960 ) for the C=C group, the wave number is 1635 cm -1 Absorbance at 1635 ) ratio (A = Ab 1635 / Ab 2960 ) B: the ratio of absorbance at the same wavenumber as A in the substrate film with the hard coat layer (B = Ab 1635 ' / Ab 2960 ') C: Wave number of 2960 cm due to C—H groups in the hard coat film -1 Absorbance at 2960 ) for the C=O group, the wave number is 1725 cm -1 Absorbance at 1725 ) ratio (C = Ab 1725 / Ab 2960 ) D: the ratio of absorbance at the same wavenumber as C in the substrate film with the hard coat layer (D = Ab 1725 ' / Ab 2960 ')

2. 2. The hard coat film according to claim 1, wherein a ratio of absorbances calculated by the following Fourier transform infrared spectrophotometer analysis (FT-IR analysis) further satisfies the following relationship (3). (3) E / F<155% (FT-IR analysis) 1. The hard coat film and a substrate film with a hard coat layer, which is the hard coat film before plasma treatment (the surface of the substrate film with a hard coat layer opposite to the substrate film of the hard coat layer is a plasma untreated surface), are prepared.

2. The infrared absorption spectrum of the hard coat film is measured from the plasma-treated surface side by a total reflection measurement method using a Fourier transform infrared spectrophotometer (FT-IR), and the infrared absorption spectrum of the substrate film with the hard coat layer is measured from the plasma-untreated surface side by a total reflection measurement method using a Fourier transform infrared spectrophotometer (FT-IR).

3. The ratio of absorbance E to absorbance F of the hard coat film and the substrate film with the hard coat layer is calculated from the infrared absorption spectra. E: Wave number of 2960 cm due to C—H groups in the hard coat film -1 Absorbance at 2960 ) The wave number due to the N-H group is 1524 cm -1 Absorbance at 1524 ) ratio (E = Ab 1524 / Ab 2960 ) F: the ratio of absorbance at the same wavenumber as E in the substrate film with the hard coat layer (F = Ab 1524 ' / Ab 2960 ')

3. A laminate film comprising the hard coat film according to claim 1 or 2 and an inorganic layer disposed on the plasma-treated surface.

4. The laminated film according to claim 3 , wherein the inorganic layer contains an indium tin composite oxide.

5. A substrate film with a hard coat layer, the substrate film including a flexible substrate film and a hard coat layer disposed on at least one side of the substrate film, the substrate film having a first side, which is a side of the hard coat layer opposite to the substrate film, and a second side, which is opposite to the first side, is prepared; a plasma treatment step of subjecting the first surface of the substrate film with the hard coat layer to a plasma treatment under a reduced pressure atmosphere in a chamber; a film-forming step of forming an inorganic layer on the first surface under a reduced pressure atmosphere following the plasma treatment step, The method for producing a laminated film, wherein the plasma treatment is a treatment with inductively coupled plasma of an oxygen-containing gas generated by application of high-frequency power to a low-inductance antenna.

6. 6. The method for producing a laminated film according to claim 5, wherein in the plasma treatment step, in the chamber, the base film with the hard coat layer is transported while being cooled or heated by a roller having a temperature control function that is in contact with the base film with the hard coat layer.

7. The method for producing a laminated film according to claim 5 , wherein the low inductance antenna has a coil shape or an open loop shape.

8. In the plasma treatment step, the plasma current density at the intermediate position between the low inductance antenna and the substrate film with the hard coat layer is set to 1.0 mA / cm 3 Above, 10mA / cm 3 The method for producing a laminated film according to claim 5, wherein:

9. The method for producing a laminated film according to claim 5 , wherein in the film-forming step, the inorganic layer is formed by a sputtering method, a deposition method or a chemical vapor deposition method.

10. The method for producing a laminated film according to any one of claims 5 to 9, wherein in the film-forming step, a conductive layer is formed as the inorganic layer.

11. The method for producing a laminated film according to any one of claims 5 to 9, wherein in the film formation step, an antireflection layer is formed as the inorganic layer, and the antireflection layer includes a plurality of transparent inorganic oxide films laminated in a thickness direction.

Citation Information

Patent Citations

  • Plasma processing apparatus

    JP2020196934A

  • Transparent electroconductive laminate

    WO2016117610A1

  • Optical film with Anti-fouling layer and method for manufacturing same

    WO2023120158A1

  • Antireflection film and image display unit

    JP2022065437A